Analysis of Electrical Properties of Activated Carbon from Empty Oil Palm Fruit Bunches (EOPFB) Against Variations in Chemical Activation Materials - Tarigan, Erna Krisda Wati Br; Pakpahan, Frada Erisa; Sari, Nirmala; Rahmawati, Rahmawati; Fadlly, Teuku Andi (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
Empty Oil Palm Fruit Bunches (EOPFB) have a high organic content such as cellulose, hemicellulose, and lignin which have the potential to be used as raw materials for activated carbon. This study aims to analyze the electrical properties of activated carbon produced from EOPFB using various chemical activation materials, namely KOH, ZnCl2, and CuCl2. The synthesis process includes drying, carbonization at 600 ℃ for 1 hour and chemical activation for 24 hours. Characteristics of diffraction patterns using X-Ray Diffraction (XRD). Electrical properties of resistivity and conductivity using the 4-point probe method. In addition, the capacitance and dielectric constant using the parallel plate method. The results of this study show that the diffraction pattern of activated carbon from EOPFB generally forms an amorphous phase.  Activated carbon with ZnCl2 chemical activation increases the electrical conductivity, which is 1.15 × 108 S/m compared to KOH at 4.1 × 10-1 S/m and CuCl2 at 1.9 × 10-1 S/m. The capacitance value increased with chemical activation of CuCl2, namely 4.44 × 10-3 F/g compared to ZnCl2 at 3.8 × 10-3 F/g and KOH at 1.06 × 10-3 F/g. The dielectric constant value of activated carbon increased by using chemical activation of CuCl2, namely 5.6 × 1010 compared to ZnCl2 of 5.3 × 1010 and KOH of 1.5 × 1010. It has potential as a dielectric material for capacitors.